The pediatric global burden of stunting: Focus on Latin America - Clara Rojas Montenegro; Gabriel Gomez; Oscar Hincapie; Svyatoslav Dvoretskiy; Tiffany DeWitt; Daniela Gracia; Juan Diego Misas (Wiley, 2022)
Abstract Introduction Stunting is a devastating consequence of poor nutrition from before birth to early childhood. While the prevalence of stunting is decreasing over the past 30 years, approximately 144 million children still suffer from stunting globally and 5 million in Latin America (LATAM). Method The purpose of this review is to provide an overview of stunting globally, with a focus on LATAM. Stunting can impact child development, lead to greater susceptibility to infections, increase functional impairments, and increase mortality risks. Furthermore, the economic negative impact of stunting is large, as stunted children will likely suffer from productivity losses due to chronic diseases in adulthood. The reduction in per capita income of the labor force due to stunting is close to 5% in LATAM; therefore, there is a continued need for comprehensive approaches to address stunting in this region and around the globe. Conclusions A multisectoral comprehensive approach to address stunting is required, with nutritional intervention being a key part of that process.